2016
DOI: 10.1186/s41029-016-0010-8
|View full text |Cite
|
Sign up to set email alerts
|

Science education reform in confucian learning cultures: policymakers’ perspectives on policy and practice in Taiwan

Abstract: This qualitative inquiry project investigates the political and policy discourses related to education reform in Taiwan. Specifically, it examines the science education reform policies and policy leaders' vision for the reform. This work also reveals the unique challenges involved in implementing contemporary science education approaches in a Confucian learning culture. Data sources included reform policy documents and interviews with policymakers. Thematic and constant comparative methods were used to analyze… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 27 publications
0
14
0
Order By: Relevance
“…Our analysis of the data revealed that the policymakers believed that certain Confucian learning traditions posed significant obstacles to the implementation of the new science curriculum, which focuses on developing innovation and critical-thinking skills in students (Huang 2014). The policy leaders who participated in our study also asserted that "the emphasis on maintaining a harmonious social order in Confucianism has led to excessive social conformity" (Huang 2014, pp.…”
Section: Understanding the Study Contextmentioning
confidence: 97%
See 4 more Smart Citations
“…Our analysis of the data revealed that the policymakers believed that certain Confucian learning traditions posed significant obstacles to the implementation of the new science curriculum, which focuses on developing innovation and critical-thinking skills in students (Huang 2014). The policy leaders who participated in our study also asserted that "the emphasis on maintaining a harmonious social order in Confucianism has led to excessive social conformity" (Huang 2014, pp.…”
Section: Understanding the Study Contextmentioning
confidence: 97%
“…The findings of this study also illuminate the various ways in which science teachers in Taiwan continue to navigate through traditional and contemporary practices in science education. Although the reform in science education was meant to bring about a fundamental shift toward constructivist pedagogy in Taiwanese classrooms (Huang 2014), many teachers in this study still believed that direct teaching would best prepare students for success in Taiwan's examination-driven learning culture. Transforming educational practice is not easy in a learning culture where respect for tradition is highly valued; it requires a significant shift in teachers' epistemological beliefs about teaching and learning.…”
Section: Discussion: Teachers Negotiating Professional Identity Durinmentioning
confidence: 99%
See 3 more Smart Citations